Langerhans and inflammatory dendritic epidermal cells in atopic dermatitis are tolerized toward TLR2 activation. Issue 11 (30th October 2018) - Iwamoto, K.; Nümm, T. J.; Koch, S.; Herrmann, N.; Leib, N.; Bieber, T.
Abstract: Background: The skin of atopic dermatitis (AD) patients presents a significant dysbalance of the microbiome with a high colonization by Staphylococcus aureus ( S. aureus ), which positively correlates with the severity of the disease. Objective: Understanding the role of epidermal dendritic cells (DC) as link between the innate and the adaptive immune systems in AD. Methods: Comparative phenotypic and functional analysis of TLR2 on Langerhans cells (LC) and inflammatory dendritic epidermal cells (IDEC) in organotypic models as well as freshly isolated cells from healthy and AD skin. Results: In situ analysis of freshly isolated LC and IDEC from AD skin revealed decreased TLR2 expression compared to LC from healthy skin. In contrast to IDEC, LC from AD skin failed to display any evidence for in situ activation. Exposure to TLR2 ligand Pam3Cys resulted in maturation and increased migratory activity of LC from normal skin. LC and IDEC from AD were unresponsive to TLR2 ligand in that they failed to mature and displayed a high spontaneous migratory activity. Keratinocytes from both healthy and AD skin expressed similar levels of TLR2. The production of IL‐6 and IL‐10 was impaired by Pam3Cys in supernatants from AD skin. IL‐18 was significantly higher in supernatants from AD skin and not influenced by TLR2 ligation, when compared to healthy skin. Conclusion: Our results suggest that TLR2‐mediated sensing of S. aureus ‐derived signals is strongly impaired in LC from AD skin. This phenomenon may partly contribute to the immune deviation in AD and the lack of S. aureus clearance. Abstract : Langerhans cells (LC) and inflammatory dendritic epidermal cells (IDEC) in atopic dermatits skin express less TLR2 compared to LC from healthy skin. Exposure to TLR2 ligand resulted in maturation and increased migratory activity of LC from normal skin. LC and IDEC in atopic dermatits skin do not respond to TLR2 activation but displayed a high spontaneous migratory activity.